Penyelenggaraan Otonomi Daerah Di Indonesia Pasca Reformasi - Suhardi, Muhammad (SOLID, 2023)
Abstract - This writing is intended to examine and analyze the administration of local government post-reform in Indonesia. It constitutes normative prescriptive research, seeking arguments based on research findings to assess what is right or wrong according to the law. Utilizing the concepts of reform, decentralization, and regional autonomy as analytical tools, the results indicate that the central government's policies towards the administration of local government post-reform have experienced fluctuations. This implies that when the central government's position is weak, substantial authority is granted to local authorities, whereas conversely, when the central government's position is strong, authority previously delegated to local entities is gradually retracted. Keywords:  Autonomy; Region; Indonesia; Reform